Interpersonal Motives in Anorexia Nervosa: The Fear of Losing One's Autonomy. Issue 3 (20th December 2012) - Brockmeyer, Timo; Holtforth, Martin Grosse; Bents, Hinrich; Kämmerer, Annette; Herzog, Wolfgang; Friederich, Hans‐Christoph
<x xml:space="preserve">Abstract</x> Objective This study examined the widely held but insufficiently studied hypothesis of autonomy disturbances in anorexia nervosa. Method A total sample of 112 participants comprising patients with acute anorexia nervosa (AN), women recovered from anorexia nervosa (REC), clinical controls (CC), and healthy controls (HC) completed measures of dependency and intimacy strivings, as well as measures of frustrations of these same strivings. Results In comparison to HC and CC, AN showed a stronger motivation to avoid dependency and lower strivings for intimacy. Compared with HC, but not with CC, AN also showed stronger frustrations of the same motives. Whereas REC did not differ from AN regarding avoidance of dependency, they reported lower frustration of dependency avoidance (i.e., less actual experiences of dependency). Finally, REC reported higher intimacy motivation as well as better satisfaction of intimacy motivation as compared with AN. Conclusions The present findings suggest that a pronounced motive of avoiding dependency may be a vulnerability factor for anorexia nervosa that is disorder‐specific and trait‐like. Frustrations of this motive seem to be associated with psychopathology.